Design of an interactive finite element computer package for the analysis of the ride of a generalised off-road vehicle - Kamar, Elsayed Abdrabboh (Cranfield University, 1987)
A versatile computer package, to evaluate ground vehicle ride comfort has been designed. Wheeled, tracked, and semitracked vehicles have been modelled. The emphasis has been placed upon the tracked vehicle suspension systems with the neatly ”standard" torsion bar arrangement operating with either telescopic or rotary-vane dampers. Substantial investigation of the four-bar linkage, associated with the rotary-vane damper, has been carried out and is presented here.The package includes linear ,nonlinear ,[2-V) ,and I3-Vj vehicle models. A new technique employing the finite element method (FEM) fat suspension system modelling has been developed. Several methods of numerical integration are available in the package .A new evident scheme based on a hypetosculatory Hermitian weighted residual of the second order for the solution of the system of differential equations which simulate the vehicle has been derived. Whenever necessary the error developed during the integration process was limited. The graphic display facility of digital computers has been used extensively in the present code. As an example, the damped eigen-value problem has been solved graphically. The graphical solution is simple, direct, and tellable compared to the analytical solution. The terrain configuration might be of either harmonic or atbitrary shape function. Two tolerence critetia have been employed fat tide comfort evaluation ,namely, the absorbed power critetion and the international standard organization ISO 2631 critetion.The two critetia are fully integrated into the package and operate automatically. All individual subroutines have been tested successfully for the purpose intended. Complete sectors have been validated by running various case studies. The results obtained from the package agree reasonably well with the analytical or experimental results. The package allows updating in response to new vehicle and vehicle-terrain technology and can be run on both time-skating or batch processing computer machines. The main package structute is independent of computer type.